Kesan persekitaran fizikal pejabat terhadap stres di tempat kerja - Samsudin, Suhana (2015)
The physical environment is important because it can causes stress to the way in which it affects the individual's needs. Better physical environment of office is agreed to produce a better employee’s performance. The first objective of this study is to examine the factors that affect the physical environment of the office stress in the workplace while the second objective is to propose actions that can reduce stress that caused from the physical environment of the office. For the survey, questionnaires were given to staff at UTM Skudai. The population in this study was non-academic staff of Universiti Teknologi Malaysia, Skudai. Samples were randomly selected (random sampling). In addition, the data obtained were analysed by Frequency Analysis methods, Distribution Analysis and Cross-tabulation Analysis. The results showed that noise, lighting, office structure, privacy, temperature, furniture, air quality, colour, outside view and accessibility of view are all factors that affect stress. This study can serve as a guide to the aspects that need to be considered in determining the design of the physical environment of the office in the future.